Let [tex]n[/tex] be the smallest of the 4 integers, so the others are [tex]n+1[/tex], [tex]n+2[/tex], and [tex]n+3[/tex]. Their product is
[tex]n(n+1)(n+2)(n+3) = n^4 + 6n^3 + 11n^2 + 6n[/tex]
Now consider the statement [tex]P(n)[/tex] that says
[tex]4 \mid n^4 + 6n^3 + 11n^2 + 6n[/tex]
(i.e. 4 divides the quartic)
Check the base case [tex]P(1)[/tex].
[tex]n=1 \implies 1^4 + 6\cdot1^3 + 11\cdot1^2 + 6\cdot1 = 24[/tex]
and 4 | 24 since 24 = 4•6
Now assume [tex]P(k)[/tex] is true. We want to use it to show [tex]P(k+1)[/tex] is also true. This requires proving
[tex]4 \mid (k+1)^4 + 6(k+1)^3 + 11(k+1)^2 + 6(k+1)[/tex]
assuming that
[tex]4 \mid k^4 + 6k^3 + 11k^2 + 6k[/tex]
Expand the quartic expression completely.
[tex](k+1)^4 + 6(k+1)^3 + 11(k+1)^2 + 6(k+1) \\\\ ~~~~~~~~ = k^4 + 10k^3 + 35k^2 + 50k + 24 \\\\ ~~~~~~~~ = (k^4 + 6k^3 + 11k^2 + 6k) + (4k^3 + 24k^2 + 44k + 24)[/tex]
The first group of terms is divisible by 4 thanks to the assumption [tex]P(k)[/tex]. The second group of terms is clearly divisible by 4, since each coefficient is a multiple of 4. So [tex]P(k)\implies P(k+1)[/tex]. QED